Warfarin‐associated fetal intracranial subdural hematoma: a case report. Issue 3 (18th May 2014) - Fujiwara, Kana; Aoki, Shigeru; Kurasawa, Kentaro; Okuda, Mika; Takahashi, Tsuneo; Hirahara, Fumiki
Key Clinical Message We present a case in which to of fetal subdural hematoma developing despite that the maternal the prothrombin time by international normalized ratio (PT/INR) during pregnancy was within the normal range.